STRATEGI ADAPTASI SOSIAL SUKU AKIT DI DESA SUNGAI UPIH KECAMATAN KUALA KAMPAR KABUPATEN PELALAWAN - Fajar Septyono; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Suku Akit in Sungai Upih is one of the remote indigenous communities in the province of Riau. Suku Akit on the Sungai Upih is ethnicities in the region Pelalawan, precisely in the district of Kuala Kampar. Suku Akit on the Sungai Upih customs still strong holds in each of their lives, can be seen from the simple life that run in small groups of them. The purpose of this study was to obtain in-depth information about the social adaptation strategies in the Suku Akit Sungai Upih and factors that influence adaptation. Therefore, the location of the research conducted in the District of Kuala Kampar. The research objectives are few people on the Suku Akit Sungai Upih who have moved from traditional fishing profession to rice farmers as the livelihood of his life. The survey results revealed that social adaptation strategy akit tribal communities on the Sungai Upih is the interaction of the group outside the community primarily through the trading system and a source of jobs. There are still a lot number of the Family Head Suku Akit who live below the poverty line and the traditional fishermen with minimal knowledge and technology. There are only a few heads of the families were trying to adapt to the way moonlighting as rice farmers, farm laborers, and workers charcoal maker. Rice farmers is one of the social adaptation strategies to do community in Suku Akit Sungai Upih to survive in meeting basic needs of the family economy.This research is expected to be beneficial for all.Keywords: Strategy, Adaptation, Remote Indigenous Communities.